Distribution of genus Glenea in Sarawak using Multiple Species Occupancy Model - NGUMBANG, JUAT; Mohd Azlan, Jayasilan (Malaysian Nature Society, 2025)
Longhorn beetles (Cerambycidae) are ecologically significant wood-boring insects, yet little is known about their diversity in Sarawak. This study assesses the occupancy, distribution, and richness of Glenea spp. using Multi Species Occupancy Modelling (MSOM) across 19 forest reserves and adjacent edge sites. From the 406 individuals recorded, 59 species were identified, including 18 newly described species. Results suggest moderate species turnover along an east–west gradient and highlight protected forests in central Sarawak as regional strongholds for several Glenea taxa. Community-level estimates show a higher likelihood of detection in morning surveys and indicate that sampling intensity remains a key driver for species detectability. By accounting for imperfect detection and site heterogeneity, the approach used in this study offers refined baseline estimates for a data-limited genus. Overall, the study demonstrates the potential of MSOM as a valuable method for monitoring poorly known beetle communities and guiding conservation strategies in Borneo’s fragmented forests.